Правовые аспекты понятий толерантности (Journal of actual problems of jurisprudence, 2019)
This article is written to investigate from different sides of view the meaning and direction of tolerance. At the same time the understanding of tolerance is valued from the legal point of view. Legal value, legal culture, legal education these are that should be fi rststeps in building the nation and civil society